1999
DOI: 10.1038/sj.neo.7900050
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Peroxisome Proferator-Activated Receptor γ (PPARγ) in Human Transitional Bladder Cancer and its Role in Inducing Cell Death

Abstract: The present study examined the expression and role of the thiazolidinedione (TZD)-activated transcription factor, peroxisome proliferator-activated receptor gamma (PPARgamma), in human bladder cancers. In situ hybridization shows that PPARgamma mRNA is highly expressed in all human transitional epithelial cell cancers (TCCa's) studied (n=11). PPARgamma was also expressed in five TCCa cell lines as determined by RNase protection assays and immunoblot. Retinoid X receptor alpha (RXRalpha), a 9-cis-retinoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 29 publications
5
107
1
5
Order By: Relevance
“…In vitro studies have shown that activation of the PPARg signaling pathway by ligands inhibits growth and induces differentiation and apoptosis in cultured cells of leukemia (Asou et al, 1999), bladder cancer (Guan et al, 1999), choriocarcinoma (Keelan et al, 1999), prostate cancer (Kubota et al, 1998), pancreatic carcinoma (Motomura et al, 2000), chondrosarcoma (Nishida et al, 2002), colon cancer (Sarraf et al, 1998), gastric cancer (Takahashi et al, 1999) and lung cancer (Tsubouchi et al, 2000). As the discovery of the PAX8-PPARg fusion gene in human follicular thyroid carcinoma and the demonstration of loss of PPARg transcription activity in the PAX8-PPARg fusion gene , there has been great interest in understanding the role of PPARg in the development and progression of follicular thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that activation of the PPARg signaling pathway by ligands inhibits growth and induces differentiation and apoptosis in cultured cells of leukemia (Asou et al, 1999), bladder cancer (Guan et al, 1999), choriocarcinoma (Keelan et al, 1999), prostate cancer (Kubota et al, 1998), pancreatic carcinoma (Motomura et al, 2000), chondrosarcoma (Nishida et al, 2002), colon cancer (Sarraf et al, 1998), gastric cancer (Takahashi et al, 1999) and lung cancer (Tsubouchi et al, 2000). As the discovery of the PAX8-PPARg fusion gene in human follicular thyroid carcinoma and the demonstration of loss of PPARg transcription activity in the PAX8-PPARg fusion gene , there has been great interest in understanding the role of PPARg in the development and progression of follicular thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, a study showed that the treatment of bladder cancer T24 cell line with the PPARg agonist troglitazone induced A-FABP. 32 In this context, the present investigation was initiated to evaluate the role of PPAR in A-FABP regulation in bladder cancer cells because PPAR have been shown to play critical role in carcinogenesis. We hypothesized that PPARg as well as PPARa and PPARb could regulate A-FABP expression in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in keeping with the suggestion that PPARg acts as a tumor suppressor gene (Nakajima et al, 2001;Smith et al, 2001;Koeffler, 2003). Mechanisms of PPARg-mediated antitumor activity by Tzds demonstrated experimentally include induction of cellular differentiation (Elstner et al, 1998;Guan et al, 1999;Kitamura et al, 1999;Chang and Szabo, 2002;Kawa et al, 2002), promotion of cell cycle arrest (Brockman et al, 1998;Kitamura et al, 1999;Motomura et al, 2000;Itami et al, 2001;Koga et al, 2001;Nakashiro et al, 2001;Takashima et al, 2001;Yin et al, 2001;Kawa et al, 2002;Hong et al, 2004;Rumi et al, 2004;Chen and Harrison, 2005), antiangiogenic effects (reviewed in Alarcon de la Lastra et al, 2004) and induction of apoptosis (Elstner et al, 1998;Kubota et al, 1998;Chang and Szabo, 2000;Tsubouchi et al, 2000;Eibl et al, 2001;Takashima et al, 2001;Yang and Frucht, 2001;Lovekamp-Swan and Chaffin, 2005;Yuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%